Internet-Based Communication - Gernsbacher, Morton Ann (Discourse Process, 2014)
Google the question, “How is the Internet changing the way we communicate?,” and you will find no shortage of opinions, or fears, about the Internet altering the way we communicate. Although the Internet is not necessarily making communication briefer (neither is the Internet making communication less formal), the Internet is manifesting our preference for writing over speaking. I propose that our preference for communicating through Internet-based text derives from a fundamental feature of writing: In contrast to speech, which is most often synchronous, text is most often asynchronous.